Formulasi dan Evaluasi Stabilitas Fisik Sediaan Facial Wash Ekstrak Etanol Daun Bintangur (Chalophyllum Inophyllum L.) - Adhisty Nurpermatasari; Ahmad Purnawarman Faisal (Poltekkes Kemenkes Padang, 2026)
Facial skin is highly susceptible to damage caused by free radicals and ultraviolet radiation; therefore, skincare products containing natural antioxidants are needed. Bintangur leaves (Calophyllum inophyllum L.) contain flavonoids, tannins, and steroids that have potential antioxidant and antibacterial activities. This study aimed to determine the best formulation and stability of a facial wash containing ethanol extract of bintangur leaves. The research used an experimental method with purposive sampling technique. Extraction was carried out using the maceration method with 96% ethanol solvent, then formulated into facial wash preparations with extract concentrations of 0.5%, 1%, and 1.5%. Evaluation included organoleptic test, homogeneity, pH, foam height, stability, and hedonic test involving 20 panelists. The results showed that all formulations met physical requirements with pH values of 6.1–6.4 and foam height of 4.6–5.2 cm and were generally preferred by panelists. In conclusion, the ethanol extract of bintangur leaves can be formulated into a stable and acceptable facial wash preparation.